Penerapan Pembelajaran Berdiferensiasi Pada Mata Pelajaran Pendidikan Pancasila dan Kewarganegaraan: Sebuah Tinjauan Pustaka Sistematis - Aryansyah, Ryan; Alfiandra, Alfiandra (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2024)
AbstractThis research analyzes how differentiated learning is implemented in Pancasila and citizenship education subjects. Differentiated learning pays attention to the differences and uniqueness that each student presents. There are four aspects of differentiated learning: content, process, product, and learning environment. Each student also has different learning tendencies or styles, such as visual, auditory, and kinesthetic. The systematic literature review (SLR) research aims to describe the application of differentiation in Pancasila and Civic Education subjects. The method used in this research is a literature study that analyzes the application of differentiated learning in Pancasila and citizenship education subjects. Various literature was obtained from multiple scientific research from 2021-2023 with the help of Google Scholar with the keyword